Inclined junctions in monolayer graphene: a gateway toward tailoring valley polarization of Dirac fermions - Shrushti Tapar; Bhaskaran Muralidharan (Materials for Quantum Technology)
Generating valley contrasts and achieving valley-specific transport of Dirac fermions in graphene are inherently challenging due to isotropic transport. In this work, we propose a tilted PN junction structure to induce anisotropic chiral transport within otherwise isotropic Dirac systems. By introducing a junction tilt, we modify the conservation conditions of pseudo-spin modes, effectively segregation valleys into distinct angular domains. The proposed electrostatically tunable method ensures efficient valley separation, significant transmission rates, and straightforward implementation. The doping-induced positive and negative refraction effects critically shape the trajectories of Dirac fermions, profoundly influencing the transport characteristics and enhancing valley polarization. We systematically optimize doping profiles to maximize valley splitting efficiency and extensively analyze key experimental parameters, including tilt angles and junction transition widths. Additionally, we investigate the system’s robustness against realistic conditions by introducing Anderson short-range edge disorder. Our analysis confirms that valley-selective transport remains resilient, thus demonstrating suitability for practical applications. This study paves the way for harnessing Dirac fermion optics to design devices capable of anisotropic chiral transport, effectively emulating the distinct transport phenomena observed in tilted Dirac–Weyl semimetals.